2006
DOI: 10.1099/mic.0.28688-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Escherichia coli nitrate transport protein, NarU, in survival during severe nutrient starvation and slow growth

Abstract: Escherichia coli K-12 strains expressing either NarU or NarK as the only nitrate transport protein are both able to support nitrate-dependent anaerobic growth. The narK gene is highly expressed during anaerobic growth in the presence of nitrate, consistent with a role for NarK in nitrate transport coupled to nitrate reduction by the most active nitrate reductase encoded by the adjacent narGHJI operon. The physiological role of NarU is unknown. Reverse transcriptase PCR experiments established that, unlike the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…In agreement with its complex regulation by known stress regulators, NR-Z is essential for long-term C-starvation survival, CSI cross-resistance to high temperature and acid pH as well as H 2 O 2 -inducible adaptive H 2 O 2 resistance (Seymour et al, 1996;Spector & Cubitt, 1992;. Clegg et al (2006) showed that in E. coli NarU accumulates in C-starved and chemostat-slow growing cells (with or without nitrate) and provides a selective advantage in the absence of the nitrate-inducible anaerobiosisinducible NarK nitrate transporter to cells during slow-growth and starvation conditions. However, their studies were carried out in the presence of (albeit limiting) nitrate concentrations.…”
Section: Scavenging and Utilization Of Alternative Carbon-energy Sourcesmentioning
confidence: 90%
See 1 more Smart Citation
“…In agreement with its complex regulation by known stress regulators, NR-Z is essential for long-term C-starvation survival, CSI cross-resistance to high temperature and acid pH as well as H 2 O 2 -inducible adaptive H 2 O 2 resistance (Seymour et al, 1996;Spector & Cubitt, 1992;. Clegg et al (2006) showed that in E. coli NarU accumulates in C-starved and chemostat-slow growing cells (with or without nitrate) and provides a selective advantage in the absence of the nitrate-inducible anaerobiosisinducible NarK nitrate transporter to cells during slow-growth and starvation conditions. However, their studies were carried out in the presence of (albeit limiting) nitrate concentrations.…”
Section: Scavenging and Utilization Of Alternative Carbon-energy Sourcesmentioning
confidence: 90%
“…Nonetheless, the importance of alternative respiratory systems in (aerobically grown) C-starved cells is supported by the finding that previously described stiA mutations are in the narZ gene. The narZ gene is the second gene of the narUZYWV operon encoding a nitrite extruder/nitrate transporter protein (NarU) and a second, so-called cryptic, nitrate reductase NR-Z (Clegg, Jiam, & Cole, 2006;. NR-Z is nitrate-unresponsive and anaerobiosis-repressed.…”
Section: Scavenging and Utilization Of Alternative Carbon-energy Sourcesmentioning
confidence: 99%
“…The proteins encoded by these genes use and regenerate reducing equivalents from fatty acids in the absence of external electron acceptors (icl, pdhA and scoA) (Boshoff & Barry, 2005), or during the microaerophilic respiration that is typical of cultures subjected to severe nutrient starvation or slow growth (ndh, narU) (Boshoff & Barry, 2005;Clegg et al, 2006). Cell wall and cell processes.…”
Section: Genes Induced After Exposure To 10x-mic Vancomycinmentioning
confidence: 99%
“…The membrane-bound nitrate reductases NarA and NarZ reduce nitrate in the cytoplasm (Berks et al, 1995a;Blasco et al, 1990;Iobbi-Nivol et al, 1990;Stewart, 1988). Nitrate reductase A is the predominant nitrate reductase when E. coli is grown under nitrate-sufficient conditions , whereas the poorly expressed nitrate reductase Z confers a selective advantage during the stationary phase or very slow growth (Iobbi et al, 1987Clegg et al, 2006). Under nitrate-limiting conditions, a periplasmic nitrate reductase (Nap) is expressed Wang et al, 1999;Stewart et al, 2002).…”
Section: Introductionmentioning
confidence: 99%